Effects of Glucomannan-Enriched, Aronia Juice-Based Supplement on Cellular Antioxidant Enzymes and Membrane Lipid Status in Subjects with Abdominal Obesity. (9th December 2014) - Kardum, Nevena; Petrović-Oggiano, Gordana; Takic, Marija; Glibetić, Natalija; Zec, Manja; Debeljak-Martacic, Jasmina; Konić-Ristić, Aleksandra
Abstract : The aim of this study was to analyze the effects of a 4-week-long consumption of glucomannan-enriched, aronia juice-based supplement on anthropometric parameters, membrane fatty acid profile, and status of antioxidant enzymes in erythrocytes obtained from postmenopausal women with abdominal obesity. Twenty women aged 45–65 with a mean body mass index (BMI) of 36.1 ± 4.4 kg/m 2 and waist circumference of 104.8 ± 10.1 cm were enrolled. Participants were instructed to consume 100 mL of supplement per day as part of their regular diet. A significant increase in the content of n-3 (P < 0.05 ) polyunsaturated fatty acids in membrane phospholipids was observed, with a marked increase in the level of docosahexaenoic fatty acid (P < 0.05 ). Accordingly, a decrease in the n-6 and n-3 fatty acids ratio was observed (P < 0.05 ). The observed effects were accompanied with an increase in glutathione peroxidase activity (P < 0.05 ). Values for BMI (P < 0.001 ), waist circumference (P < 0.001 ), and systolic blood pressure (P < 0.05 ) were significantly lower after the intervention. The obtained results indicate a positive impact of tested supplement on cellular oxidative damage, blood pressure, and anthropometric indices of obesity.